A Theological and Scriptural Basis for Laylayan Theology - Castillo, Fides A. del ca. 20./21. Jh. (International bulletin of mission research, 2024)
This paper aims to deepen the understanding of laylayan theology by examining its foundations in sacred scriptures and teachings of the Catholic Church. Among the myriad approaches in Asian theologizing, laylayan theology appropriates a Filipino cultural concept to articulate the lived religion of those on the peripheries. Through reflection on the scriptures, church teachings, and theological concepts concerning the marginalized, laylayan theology seeks to foster a dialogical imagination among the community of missionary disciples. It emphasizes the importance of attentively listening to and amplifying marginalized voices. In the spirit of synodality, all Christians, by their vocation, competence, and experiences, are on “mission on this earth” and called to bear witness to the Kingdom of God.